Leadless Pacemaker Implantation in the Presence of the Bioprosthetic Tricuspid Valve: Case Presentation and Literature Review - Mahsa Mohammadi; MohammadReza Iranian; Sedigheh Saedi; Yaser Toloueitabar; Amirfarjam Fazelifar; Majid Haghjoo (Clinical Case Reports)
ABSTRACT A 21‐year‐old man, known case of the repaired congenital heart disease, developed complete atrioventricular block (AVB) one week after simultaneous bioprosthetic pulmonary and tricuspid valve replacement and atrial septal defect repair. Considering the persistence of the AVB, it was decided to implant a permanent pacemaker. After considering all available options and the issues related to the patient, it was decided to implant a leadless pacemaker (LLP). A Micra pacemaker was implanted successfully, and the patient was discharged in good condition and without any complications. Follow‐up evaluation showed appropriate LLP and bioprosthetic valve functioning. Limited prior experiences and the present report showed that LLP appears to be an ideal option in the patients with bioprosthetic tricuspid valve complicated by conduction disorders.